(3ef GdJQJjH aj GdaQGFVs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3GdcdGFj , eMeO Hf TQa Hf YGOj GdbQTj GdRHjQj, TeS GdOjf , CHh YHO Gddg,J (B777 (3g` s ((3eMeO Hf bGSe Hf eMeO GdYHOdi s)
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai hHYO aEf cJGH GdeLehY ai Yde GdaQGFV s
(3BNQgG (B:s
(3KdGKI CKeGf hhGMO hjfRd efRdI GdSGbi JaQb Hjf YTGbi hGddg SHMGfI hJYGdi CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1605 (3Cf GdeLehY ai Yde GdaQGFV gh deDdag CHh YHO Gddg TeS GdOjf eMeO Hf TQa GdcdGFi GdaQV GdTGaYi GdeJhai SfI (B777 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B66s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs